Infiltration Between Popliteal Artery and Capsule of the Knee Block to Augment Continuous Femoral Nerve Catheter for Adolescent Anterior Cruciate Ligament Reconstruction: A Case Series. Issue 2 (15th January 2020) - Nguyen, Kim T.; Marcelino, Ryan; Jagannathan, Narasimhan; Suresh, Santhanam; Sawardekar, Amod
Abstract : Infiltration between popliteal artery and capsule of the knee (IPACK) is a novel technique that can provide additional analgesic relief, although there are no studies to date in the adolescent population. In 3 adolescent patients undergoing anterior cruciate ligament surgery, IPACK block augmented continuous femoral nerve block by providing posterior knee analgesia with no or only minimal opioid needs in the post-anesthesia care unit and did not produce sciatic motor weakness.